2022
DOI: 10.3389/fendo.2022.1080383
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransduction regulates inflammation responses of epicardial adipocytes in cardiovascular diseases

Abstract: Adipose tissue is a crucial regulator in maintaining cardiovascular homeostasis by secreting various bioactive products to mediate the physiological function of the cardiovascular system. Accumulating evidence shows that adipose tissue disorders contribute to several kinds of cardiovascular disease (CVD). Furthermore, the adipose tissue would present various biological effects depending on its tissue localization and metabolic statuses, deciding the individual cardiometabolic risk. Crosstalk between adipose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 212 publications
0
0
0
Order By: Relevance
“…Several mechanoregulatory proteins have roles in adipocyte differentiation and function. Yes-associated protein (YAP) and the transcriptional coactivator with PDZ-binding motif (TAZ) are transcriptional cofactors of the Hippo pathway that bind to the transcriptional enhanced associate domain (TEAD) family of transcriptional factors and are key regulators in the differentiation of mesenchymal stem cells (MSCs) [ 51 , 52 , 53 , 54 ]. The phosphorylation of YAP leads to its retention in the cytoplasm and its subsequent degradation, and these events are associated with an adipogenic phenotype ( Figure 2 ).…”
Section: Adipocyte Mechanobiologymentioning
confidence: 99%
“…Several mechanoregulatory proteins have roles in adipocyte differentiation and function. Yes-associated protein (YAP) and the transcriptional coactivator with PDZ-binding motif (TAZ) are transcriptional cofactors of the Hippo pathway that bind to the transcriptional enhanced associate domain (TEAD) family of transcriptional factors and are key regulators in the differentiation of mesenchymal stem cells (MSCs) [ 51 , 52 , 53 , 54 ]. The phosphorylation of YAP leads to its retention in the cytoplasm and its subsequent degradation, and these events are associated with an adipogenic phenotype ( Figure 2 ).…”
Section: Adipocyte Mechanobiologymentioning
confidence: 99%
“…showed that RvD1 activates anti-inflammatory molecules in synoviocytes by activating Hippo-YAP signalling pathway, thus leading to YAP cytoplasmic sequestration and proteasomal degradation [123]. Notably, this is of great interest in the context of OA, given that the inhibition of YAP has been proposed as a mechanism to prevent OA development [125], and in Ob, given that it is increased in response to these mechanical changes in hypertrophic adipocytes [126].…”
Section: Effect Of N-3 Pufas In Oboa: Focus On Anti-inflammatory and ...mentioning
confidence: 99%
“…On the other hand, cytokines and growth factors can influence how cells respond to mechanical stress. By controlling the synthesis and function of mechanosensors, cytoskeletal elements, and integrins, they can modify the receptivity of endothelial cells to mechanical stimuli [237][238][239].…”
Section: Cytoskeletal Rearrangementsmentioning
confidence: 99%
“…In hypertension-related endothelial dysfunction, NO bioavailability is reduced, oxidative stress is increased, inflammatory processes are triggered, and the endothelial barrier function is impaired. According to Liu et al [239] and Gallo et al [254], these changes lead to vasoconstriction, increased vascular tone, and decreased vasodilation, contributing to the maintenance of hypertension.…”
Section: Endothelial Dysfunction In Hypertensionmentioning
confidence: 99%